Pattern of Neonatal Admissions and Outcome in an Intensive Care Unit (ICU) of a Tertiary Care Paediatric Hospital in Bangladesh A One-Year Analysis - Hoque, MS; Alam, S; Ahmed, ASMNU (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Objective: To describe the characteristics of neonates admitted to intensive care unit (ICU) and their outcome in a tertiary care paediatric hospital in Bangladesh. Study Design: Retrospective, descriptive study. Setting and Duration of Study: Paediatric intensive care unit in Dhaka Shishu Hospital from January to December 2011. Methods: Data was retrieved from file records of all admitted neonates regarding age, gender, gestational age, birth and admission weight, reason for admission and outcome. Results: During this study period, the total number of patients admitted was 191; most of them were neonates (146, 76.4%). Among the 146 neonates, the highest number comprised of birth asphyxia (55, 37.7%), followed by serious bacterial infections (sepsis, pneumonia, meningitis) (30, 20.5%) preterm low birth weight (LBW) babies (28, 19.2%), surgical conditions (congenital diaphragmatic hernia, oesophageal atresia with trachea-oesophageal fistula, Hirschsprung disease and anorectal malformations) (18, 12.3%), respiratory distress syndrome (RDS) (9, 6.2%), and congenital heart disease (6, 4.1%). Out of 146 patients, 42 expired (28.8%). Most of the expiries were due to sepsis (35.7%); followed by prematurity (21.4%), perinatal asphyxia (19.0%) and surgical conditions (14.3%). Conclusion: Birth asphyxia, septicaemia, and prematurity were the main reasons for neonatal admissions in ICU, while case fatality was highest for septicaemia. Regular antenatal visits, safe delivery practice and timely referral to tertiary care hospitals may result in decreased burden in ICU and also better outcome. DOI: http://dx.doi.org/10.3329/jbcps.v31i3.20979 J Bangladesh Coll Phys Surg 2013; 31: 134-139